2012
DOI: 10.3109/02652048.2012.692400
|View full text |Cite
|
Sign up to set email alerts
|

Brain targeting of Atorvastatin loaded amphiphilic PLGA-b-PEG nanoparticles

Abstract: The objective of this study was to develop polysorbate 80 coated and Atorvastatin loaded poly(lactic-co-glycolic acid)-block-poly(ethylene glycol) (PLGA-b-PEG) nanoparticles and to investigate advantages of coating on nanoparticles for brain delivery of Atorvastatin. The nanoparticles were prepared by nanoprecipitation method. The effects of polymer concentration, PEG content and polysorbate 80 coating on the particle size, drug loading efficiency and release behaviour of nanoparticles were investigated. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…[396] Amphiphilic NPs, however, have been found to be effective at prolonging circulation time and improving brain drug delivery in vivo without causing significant toxic effects (Figure 38). [449,497,498] Figure 38. Schematic illustration of the structure of an amphiphilic NP self-assembled from its constituent polymers.…”
Section: Diphtheria Toxin Receptor (Dt R )mentioning
confidence: 99%
“…[396] Amphiphilic NPs, however, have been found to be effective at prolonging circulation time and improving brain drug delivery in vivo without causing significant toxic effects (Figure 38). [449,497,498] Figure 38. Schematic illustration of the structure of an amphiphilic NP self-assembled from its constituent polymers.…”
Section: Diphtheria Toxin Receptor (Dt R )mentioning
confidence: 99%
“…We used dichloromethane (DCM) and chloroform because of the slight miscibility with water and therefore micro droplets were obtained. Poly (lactic-co-glycolic acid)-poly ethylene glycol (PLGA-b-PEG) diblock copolymer was used as the polymeric material, since it is widely used in biomaterials research because of its biocompatible and biodegradable properties [23][24][25] . In addition, once the porous PLGA-b-PEG construct is obtained, it preserves its structural integrity without any need for second crosslinking step.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PEGylation is still the most widely used strategy method because a strategy cannot be used to enhance the circulation half-life of all kinds of NPs in the blood cells (Huang et al, 2016). It was stated that the PEG layer around the NPs reduced the adsorption of opsonins and other serum proteins could be reduced by the presence of PEG on the surface of NPs (Vannucci et al, 2012, Xin et al, 2012, Simsek et al, 2013). Here we found that the unmodified Qdots which carry PEG amine on its surface showed a high accumulation in the liver, which cannot explain the long circulation time of the formulated Qdots-VAP because VAP binds to the SSTR2 expressed in blood cells (Bhathena and Recant, 1980, Perez et al, 2003, Lichtenauer-Kaligis et al, 2004, Petrak, 2005, Reynaert et al, 2007, ter Veld et al, 2007, Muscarella et al, 2011).…”
Section: Discussionmentioning
confidence: 99%